Cholera Toxin Mimics Melanocyte Stimulating Hormone in Inducing Differentiation in Melanoma Cells - O'Keefe, Edward (1974)
Cholera toxin (choleragen) and melanocyte stimulating hormone alter within hours the morphology of melanoma cells in culture, and they slow the growth of serum-stimulated cells. After 7-10 days, cells exposed to choleragen or hormone show increased size and a fibroblastic growth pattern. Tyrosinase (EC 1.14.18.1; monophenol monooxygenase) activity increases after 3 days in the presence of 10(-8) M hormone or 10(-10) M choleragen. Binding studies with (125)I-labeled choleragen indicate that although a melanoma cell can bind a maximum of 10(6) molecules of cholera toxin, only about 4000 binding sites must be occupied to achieve maximum stimulation of tyrosinase activity. Melanocyte stimulating hormone and choleragen probably have different membrane-binding sites. After exposure to choleragen for 5 min, membrane adenylate cyclase (EC 4.6.1.1) activity increases dramatically upon further incubation of intact cells for several hours at 37° and falls slowly to basal values over a period of more than 10 days. Hormone stimulation of adenylate cyclase is rapidly reversed by washing the cells, but subsequent restimulation of cyclase by the hormone is impaired. These studies indicate that cAMP mediates the effects of melanocyte stimulating hormone on growth and morphology as well as on tyrosinase activity. Cholera toxin may permanently activate the available adenylate cyclase molecules, and the protracted decay of stimulation that follows may reflect the biological turnover of adenylate cyclase molecules in these cells.